Day 3 Wed, February 23, 2022 2022
DOI: 10.2523/iptc-22485-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Optimization of CO2 Foamed Chelating Stimulation Fluids at High-Pressure, High-Temperature, and Salinity

Abstract: Foamed acidic fluids have been utilized in the industry for enhanced oil recovery and fracturing applications due to their various advantages. Flowback enhancement, recovery of treatment fluids, and reduction of overall water consumption per operation are examples of these advantages. This study examines the utilization of a chelating agent, L-glutamic acid-N, N-diacetic acid (GLDA) in N2 and CO2 foamed fluids, which enhances the stability of foamed acidic fluids, lowers corrosion tendency, and is environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Because the viscosity of both solutions changed when GLDA was added, these findings demonstrate that sulfate ions regulate the seawater rheology . The chelating agent GLDA has been studied for its potential to lessen corrosion in foamed acidic fluids made from nitrogen dioxide (N 2 ) and carbon dioxide (CO 2 ), to increase fluid stability, and to lessen environmental effects . The results showed that GLDA helped the foamed fluid become more stable and, it increased its viscosity.…”
Section: Chelating Agents Effects On Seawater Fluidmentioning
confidence: 95%
See 4 more Smart Citations
“…Because the viscosity of both solutions changed when GLDA was added, these findings demonstrate that sulfate ions regulate the seawater rheology . The chelating agent GLDA has been studied for its potential to lessen corrosion in foamed acidic fluids made from nitrogen dioxide (N 2 ) and carbon dioxide (CO 2 ), to increase fluid stability, and to lessen environmental effects . The results showed that GLDA helped the foamed fluid become more stable and, it increased its viscosity.…”
Section: Chelating Agents Effects On Seawater Fluidmentioning
confidence: 95%
“… 45 The chelating agent GLDA has been studied for its potential to lessen corrosion in foamed acidic fluids made from nitrogen dioxide (N 2 ) and carbon dioxide (CO 2 ), to increase fluid stability, and to lessen environmental effects. 75 The results showed that GLDA helped the foamed fluid become more stable and, it increased its viscosity. The generated viscosities ranged from ∼5 to ∼25 cP throughout a broad shear speed range.…”
Section: Chelating Agents Effects On Seawater Fluidmentioning
confidence: 97%
See 3 more Smart Citations